Comparison of survival time of three adhesive materials used in fixed space maintainer cementation by using ball milling machine: An in vitro study - Zaidan , Sara M; Rafeeq , Reem A; Başaran , Bahri (Journal of Baghdad College of Dentistry, 2024)
Background: Premature primary tooth extraction causes loss of arch length, therefore; space preservation is a critical step to prevent space closure that can lead to future malocclusion. This can be achieved by using a space maintainer. Thus study’s objective was to assess and contrast the survival of three different luting materials used to cement fixed space maintainers an in vitro study. Materials and Methods: This study used 30 extracted human third molars without caries, cracks, or chemical pretreatment. They were divided into three groups of ten samples (n = 10). The adhesives selected in this study were Relyx Luting 2 (resin modified glass ionomer), TOTALCEM (self-etching, self-adhesive, resin cement, dual cure) and Transbond Plus Light Cure band adhesive (compomer). Manufacturer recommendations for bonding were followed after cleaning and polishing for all surfaces of the teeth. To distinguish the specimens, the middle of the root was drilled with a handpiece and marked with a red marker, then incubated for 24 h at 37 °C before being transferred to a ball mill machine to induce mechanical stress. The machine was opened to check for any failed specimen. This continued until all bands were removed from the teeth. The data was analyzed using log-rank Kaplan-Meier and Bonferroni post hoc tests at p 0.05. Results: the mean survival time of bands cemented with TOTALCEM and RelyX Luting 2 significantly longer than bands cemented with Transbond Plus Light Cure band adhesive (P<0.001). Conclusion: band retention with TOTALCEM and RelyX Luting2 superior than bands cemented with Transbond Plus Light Cure Band Adhesive.